2018
DOI: 10.1016/j.elecom.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of copper(I) oxide reduction/oxidation in atmospheric pressure plasma jet

Abstract: We describe the controlled reduction of copper(I) oxide films to metallic copper in a nonthermal, atmospheric pressure, helium plasma jet. Thin layers (≈ 0.1 m) of Cu2O are electrochemically deposited onto Pt electrodes and placed in capacitively coupled helium plasma doped with H2, O2 and CH4 gases. Ex-situ Raman spectroscopy was used to probe the effect of plasma treatment on the deposited copper oxide layer. We show that application of a static bias voltage to the Pt substrate during plasma exposure can co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Plasma can supply the right ingredients to induce non-thermal electrochemical reaction in the gas/solid phase. The electrochemical reduction of Cu2O by atmospheric pressure plasma jets has been already shown even in absence of hydrogen [10]. In this condition, the reduction reactions which can occur in our experiment can be summarised as…”
Section: Model Of the Reduction Mechanismsupporting
confidence: 51%
See 2 more Smart Citations
“…Plasma can supply the right ingredients to induce non-thermal electrochemical reaction in the gas/solid phase. The electrochemical reduction of Cu2O by atmospheric pressure plasma jets has been already shown even in absence of hydrogen [10]. In this condition, the reduction reactions which can occur in our experiment can be summarised as…”
Section: Model Of the Reduction Mechanismsupporting
confidence: 51%
“…The results obtained allowed to review the layered structure of the corroded layers at the sub-µm level, highlighting its evolution as a function of the corrosion process and the following plasma cleaning stage. In addition, this improved description of the surface evolution permitted to suggest an extension of the electrochemical metal oxides reduction mechanism introduced in the electronics field [10] to Ag,Cu sulphides. The proposed model highlights the complementary action of hydrogen atoms and electrons for silver sulphide and copper monosulphide reduction and explains the unsuccessful result on Cu2S.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 We have shown that helium plasma at atmospheric pressure in the absence of hydrogen was effective at reducing copper oxide films, suggesting that electrons alone are, in the case of copper, sufficient for the reduction process. 17 This view is supported by Lee et al 18 and Sui et al 19 who loaded metal ions in a polymer matrix and showed using an APPJ that the reduction of the metal ions was indeed driven by plasma (or secondary) electrons.…”
Section: Introductionmentioning
confidence: 85%
“…We know from plasma exposure of copper oxide that hydrogen (radical or otherwise) was not necessary for the reduction process, but speeds up the reduction process. 17 Therefore, the excited electrons (either plasma or secondary electrons) are key for the reduction process.…”
Section: Discussionmentioning
confidence: 99%